(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The yield of vines in a vine depends on the number of vines per unit area or per hectare, the average weight of each vine on the number of vines available on these vines. Options with high performance on these factors will always yield a higher yield per unit of land.